Factors driving thrips pressure across strawberry-growing regions in Switzerland - Lucien Schneeberger; Angelos Mouratidis; Virginie Dekumbis; Lindsey Norgrove; Louis Sutter (Journal of Pest Science, 2026)
Thrips are important pests of everbearing strawberries worldwide. The emergence of resistance and the ban on several active ingredients mean that alternatives to insecticides need to be developed. Augmentative biological control in many cases has proved successful in controlling thrips; however, in certain cases it fails to keep thrips below the economic damage threshold. Identifying key factors influencing thrips populations is essential. We aimed to assess how thrips population dynamics varied by thrips species, grower practice and location of strawberry plots. In 2022 and 2023, a network of 43 plots in all the main strawberry-growing regions of Switzerland was established. Thrips were counted, adults identified to species level, and the management practices of the growers as well as the crops, topography and temperatures of the plots were recorded. The main species were Frankliniella occidentalis (68% of samples), Thrips tabaci (13%), F. intonsa (12%), and T. fuscipennis (5%) in varying proportions from one plot to another. Only the environmental factors altitude, temperature and distance from a meadow explained a sufficient proportion of thrips population variability. We also observed a link between the distance to the forest and the extent of damage done by thrips to strawberries. No differences were detected between the control strategies used suggesting that the use of insecticides or biocontrol agents is similarly effective. These results underscore the importance of considering the landscape and surrounding host plants in thrips management strategies.